Melatih Literasi Digital Peserta Didik Melalui PBL Berbasis Etno-STEM Berbantuan Augmented Reality - Prelia Dwi Amanah; Satutik Rahayu; Gunawan Gunawan (Indonesian Publication Center, 2026)
This community service program aimed to train junior high school students’ digital literacy through the implementation of Problem-Based Learning (PBL) integrated with Ethno-STEM and supported by Augmented Reality (AR). The program was motivated by students’ limited ability to access, evaluate, and use digital information critically, as well as the lack of contextual technology integration based on local wisdom. The activities were conducted through planning, implementation, observation, and evaluation-reflection stages, including teacher training, classroom mentoring, and the use of PBL-based Ethno-STEM modules assisted by AR on the topic of motion and force. The participants consisted of two science teachers and 82 students. Data were collected using learning implementation observations, digital literacy questionnaires, and reflective discussions. The results show that the learning activities were implemented properly and students demonstrated a tendency toward improved digital literacy, particularly in accessing relevant digital sources, evaluating information credibility, and using digital technology to support their understanding of science concepts. In addition, problem-based learning contextualized with local culture and enhanced by AR visualization increased student engagement. Therefore, PBL integrated with Ethno-STEM and supported by AR has the potential to serve as an alternative strategy for strengthening digital literacy in science learning.